2004
DOI: 10.1016/j.bbamem.2003.11.019
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics study of the KcsA channel at 2.0-Å resolution: stability and concerted motions within the pore

Abstract: The stability of the KcsA channel accommodating more than one ion in the pore has been studied with molecular dynamics. We have used the very last X-ray structure of the KcsA channel at 2.0-A resolution determined by Zhou et al. [Nature 414 (2001) 43]. In this channel, six of the seven experimentally evidenced sites have been considered. We show that the protein remains very stable in the presence of four K+ ions (three in the selectivity filter and one in the cavity). The locations and the respective distance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
57
0

Year Published

2007
2007
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(60 citation statements)
references
References 35 publications
3
57
0
Order By: Relevance
“…The crystal structures of KcsA, MthK, KvAP, and KirBac1.1 indicate that all these K ϩ channels share almost identical selectivity filter structures and very similar inner cavities lined by the M2 (S6) helices (7,8,33,34). It has long been recognized that complete removal of K ϩ will cause K ϩ channels to permanently lose their K ϩ selectivity or ion permeation capacity as a result of collapse or distortion of the selectivity filter (35)(36)(37), and molecular dynamics simulations suggest that the residence of K ϩ ions plays a critical role in stabilizing the structure of the selectivity filter of KcsA (9,12,21). Such a stabilizing effect conferred by the permeant ionoxygen ring coordination is likely a property of all K ϩ channels (11,21).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The crystal structures of KcsA, MthK, KvAP, and KirBac1.1 indicate that all these K ϩ channels share almost identical selectivity filter structures and very similar inner cavities lined by the M2 (S6) helices (7,8,33,34). It has long been recognized that complete removal of K ϩ will cause K ϩ channels to permanently lose their K ϩ selectivity or ion permeation capacity as a result of collapse or distortion of the selectivity filter (35)(36)(37), and molecular dynamics simulations suggest that the residence of K ϩ ions plays a critical role in stabilizing the structure of the selectivity filter of KcsA (9,12,21). Such a stabilizing effect conferred by the permeant ionoxygen ring coordination is likely a property of all K ϩ channels (11,21).…”
Section: Discussionmentioning
confidence: 99%
“…It has long been recognized that complete removal of K ϩ will cause K ϩ channels to permanently lose their K ϩ selectivity or ion permeation capacity as a result of collapse or distortion of the selectivity filter (35)(36)(37), and molecular dynamics simulations suggest that the residence of K ϩ ions plays a critical role in stabilizing the structure of the selectivity filter of KcsA (9,12,21). Such a stabilizing effect conferred by the permeant ionoxygen ring coordination is likely a property of all K ϩ channels (11,21). Krishnan et al (17) have shown that multiple permeant ions not only stabilize the selectivity filter but also stabilize the channel tetramer itself in KcsA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The correct positioning of the protein with respect to the bilayer is crucial for the success of the above-reported procedure, and this is usually achieved by maximizing the contacts between aromatic side chains and lipid headgroups. 63,64 However, the hERG primary sequence ranging from S5 to S6 did not allow this unbiased approach, therefore we preferred to first insert the well-studied KcsA template according to Carloni and coworkers, 64 and then to coherently superimpose the models (fitting against the SF Ca atoms: RMSD KcsA/hERG C 5 0.13 Å ; RMSD KcsA/hERG O 5 0.11 Å ).…”
Section: Protein Setupmentioning
confidence: 99%
“…[68][69][70] This process often occurs when there is a mismatch between the equilibrium positions ͑minima͒ of the adsorbate-lattice interaction and the adsorbate-adsorbate interaction. 65,66 In situations where the adsorbate-adsorbate interaction is mainly repulsive, concerted diffusion can become viable if there are many metastable positions of the adsorbates with almost similar energies.…”
Section: Diffusion Of Lithium Inside the (55) Nanotubementioning
confidence: 99%